Neutrophil/lymphocyte ratio: a potential biomarker in patients with head and neck squamous cell carcinoma treated with immune checkpoint inhibitors - Caterino, Marianna; Lo Giudice, Giorgio; Damiano, Vincenzo; Perri, Francesco; Giordano, Guido; Ciardiello, Davide; Mirabile, Aurora; Pirozzi, Mario; Sponghini, Andrea Pietro; Ricci, Vincenzo; Montella, Liliana; Addeo, Raffaele; et al. (Frontiers in Oncology, 2025)
IntroductionLiterature has shown that there is a correlation between increased circulatory inflammatory factors and negative prognosis, which can be evaluated through the using the neutrophil and lymphocyte ratio (NLR). The aim of this research is to investigate the predictive and prognostic role of the NLR in recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC) patients, treated with immunotherapy, and its correlation to the overall survival (OS), progression free survival (PFS) and objective response rate (ORR).MethodsThis multicentric study coordinated by the Oncology Unit of University of Campania “Luigi Vanvitelli”, retrospectively analyzed data from 135 patients diagnosed with R/M HNSCC from 13 Italian oncological centers.ResultsTwo groups were made using the median NLR value of 4.2. 71 patients (52.6%) had NLR>4 and 64 patients (47.4%) had NLR<=4. Mean OS of patients with NLR>4 was significantly shorter than that of patients with NLR<=4 (23.1 vs 37.4 months, p= 0.002). Univariable analysis showed a statistically significant correlation between OS and NLR value (p=0.002), and between OS and ECOG (p=0.022). Median PFS stratified by NLR value, was statistically significant: 6.5 vs 20 months in patients with NLR>4 and NLR<=4, respectively (p= 0.013O). ORR in the general population was 32.6%. NLR-stratified ORR confirmed the unfavorable prognostic role of high NLR: 20% if NLR<=4, and 12.5% if NLR>4.DiscussionBasal NLR value lower than the cut-off of 4 is independently associated with better OS, PFS and ORR in patients with R/M HNSCC treated with immunotherapy, in first- or second- line.